Deciding Where to Turn: A Qualitative Investigation of College Students’ Helpseeking Decisions After Sexual Assault - DeLoveh, Heidi L. M.; Cattaneo, Lauren Bennett (American journal of community psychology, 2017)
Sexual assault is a widespread problem on college campuses that has been the subject of substantial attention in recent years (Ali, 2011; Krebs, Lindquist, Berzofsky, Shook‐Sa, & Peterson, 2016). Resources designed to address the problem exist, but there is evidence that they are underutilized by survivors (Campbell, 2008). The current study used grounded theory to explore how sexual assault survivors make decisions about helpseeking. In‐depth interviews were conducted with 14 college sexual assault survivors to develop a theoretical model for their decision‐making process. The resulting model, Deciding Where to Turn, suggests that survivors engage in three key decision points: determining if there is a problem related to the sexual assault (Do I Need Help), considering options (What Can I Do), and weighing the consequences of these options (What Will I Do). This process results in one of four behavioral choices: cope on one's own, seek support from friends/family, seek support from formal resources, or covert helpseeking, where needs are met without disclosure. Deciding Where to Turn contributes to the literature by providing a framework for understanding helpseeking decisions after sexual assault, highlighting the need to match reactions to survivor perceptions. The concept of covert helpseeking in particular adds to the way researchers and practitioners think about helpseeking. Research and practice implications are discussed. Highlights Provides a theoretical model of survivors’ helpseeking decisions from their own perspectives. Links most of the commonly cited helpseeking correlates to particular points in the process. Identifies covert helpseeking as a meaningful category of behavior and area for future research. Highlights survivors’ concerns about both over‐ and under‐reactions from help providers. Provides evidence in support of and contrary to conclusions that formal services are underutilized.